PENURUNAN COD DAN TSS PADA LIMBAH LAUNDRY MENGGUNAKAN ELEKTRODA ALUMINIUM (Al) DAN TEMBAGA (Cu) PADA METODE ELEKTROKOAGULASI - Mirna Desyderia Sumawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2021)
A research about reduction of COD and TSS from laundry waste with Electrocoagulation method using Al and Cu electrodes in COD and TSS reduction parameters has been done. In this research, the voltage and optimum time determited based on occurred in electrocoagulation process. The determination of COD and TSS in the contact time was 60 minutes with the value of COD was 90.5645% and TSS 63.7279%. The value of voltage optimum was 12 Volt, obtain COD was 90.2392% and TSS 60.7052%.